SALAT QABLIYAH DAN BA’DIYAH DALAM PANDANGAN ULAMA HADITH - Aniqoh Aniqoh; Mahmud Nasir (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2021)
Hadith has a central position in Islam. It is the second source after the Qur'an, which functions to detail the messages of the Qur'an that are mujmal, so that clear information is obtained in carrying out daily worship practices, including Qabliyah and Ba'diyah prayers. However, in fact, the hegemony of fiqh thought is thicker than the understanding of hadith in determining the practice of worship for Muslims, especially Indonesian Muslims. Fiqh seems to be the first and main benchmark in dealing with problems. Therefore, the researcher will present how the hadith actually describes the af'aliyah of the Prophet regarding the pure Qabliyah and Badiyah prayers in accordance with the views of hadith scholars. In this study, the method used is the thematic hadith method. Namely, by collecting the same hadiths that discuss the Qabiliyah and Badiyah prayers of the Prophet. In this study, before moving on to understanding hadith, the validity of the quality of hadith will be explained, so that it can be used as a guide for interpretation. The local hadith research is the al-tis'ah polar book, while the understanding is taken from the sharh book of hadith. From the results of the study, it was explained that the Prophet carried out the Qabliyah and Ba'diyah prayers: Qabliyah dawn as much as two raka'at and after that he slept lightly until the muezzin iqamat. Qabliyah Dhuhur carried out two raka'at and sometimes four raka'at. While Ba'diyah Dhuhur he carried out two raka'at. Qabliyah 'Asar he carried out four raka'at with two greetings. For Qabliyah Maghrib, the Messenger of Allah ordered to run it for those who wished, but with a note that it should not be considered as a confirmed Sunnah. While Ba'diyah Maghrib, runs two raka'at. While Ba'diyah 'Isha, he runs two raka'at.",